The Effect of Message Framing of Other Distribution Channels on Purchase Intention in TV Home Shopping: Focused on the Moderating Effect of Product Type (Luxury vs. General ) - Park, Dong-Hyun; Natlada, Wiseswongsa,; Kim, Gwi-Gon (Journal of Ecohumanism, 2024)
This study investigates the influence of message framing of other distribution channels on product attitudes and purchase intentions for TV home shopping products. The research explores the mediating effects of perceived quality, perceived price, and persuasion knowledge in relation to message framing and product attitudes. Additionally, it examines the moderating effects of product type (luxury vs. general products). Finally, the study empirically analyzes the effect of product attitudes on purchase intentions. A survey was conducted with 359 participants, including residents and university (graduate) students from Daegu and Gyeongbuk, and the data were analyzed using ANOVA and regression analysis with SPSS 21.0. The results indicate that, firstly, the message framing of other distribution channels for TV home shopping products affects purchase intentions. Particularly, message framing related to premium department stores has a greater effect on perceived quality, perceived price, and persuasion knowledge than regular department stores. Secondly, perceived quality, perceived price, and persuasion knowledge related to message framing of other distribution channels for TV home shopping products positively influence product attitudes. Thirdly, product attitudes toward TV home shopping products positively affect purchase intentions. Fourthly, only the moderating effect of product type (luxury vs. general) on the effect of message framing on perceived quality was found to be significant for shoe products. These findings suggest that TV home shopping companies need to actively use message framing of other distribution channels as a marketing strategy to enhance product attitudes. However, future studies should expand the scope beyond TV home shopping channels to include various distribution channels.